2013
DOI: 10.1371/journal.pone.0062350
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormones Related to Host Plant Manipulation by a Gall-Inducing Leafhopper

Abstract: The maize orange leafhopper Cicadulina bipunctata (Hemiptera: Cicadellidae) induces galls characterized by growth stunting and severe swelling of leaf veins on various plants of Poaceae. Previous studies revealed that galls are induced not on feeding site but on distant, newly extended leaves during the feeding, and strongly suggested that some chemicals injected by the leafhopper affect at the leaf primordia. To approach the mechanism underlying gall induction by C. bipunctata, we examined physiological respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 38 publications
2
35
0
Order By: Relevance
“…Tokuda et al 2013). A sufficient pretreatment procedure permits analysis with small amounts of plant tissue or thallus (~20-100 mg dry weight) (Mikami et al 2016).…”
Section: Simultaneous Analysis Of Multiple Phytohormonesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tokuda et al 2013). A sufficient pretreatment procedure permits analysis with small amounts of plant tissue or thallus (~20-100 mg dry weight) (Mikami et al 2016).…”
Section: Simultaneous Analysis Of Multiple Phytohormonesmentioning
confidence: 99%
“…Recent advances in techniques to analyze phytohormones using liquid chromatography-mass spectrometry (LC-MS) allow simultaneous analysis of multiple hormones for a comprehensive view of phytohormone dynamics (for example, Tokuda et al 2013, Schäfer et al 2016. Despite these advances, no comprehensive analysis of phytohormones has yet been carried out in red seaweeds.…”
Section: Introductionmentioning
confidence: 99%
“…Höglund et al (2015) demonstrated that willow resistance to a gall midge was rather due to a lack of induced susceptibility than to an induced HR. Likewise, in some plant-gall-inducer systems, resistance is related to a failure in the manipulation of plant hormones concentrations (Matsukura et al 2012;Tokuda et al 2013).…”
Section: Resistance Mechanismsmentioning
confidence: 99%
“…Likewise, a detailed monitoring of early events during the onset of compatible and incompatible interactions could be performed. In particular, monitoring the accumulation of phytohormones involved in stress signaling, like jasmonic acid, ethylene and salicylic acid, and phytohormones potentially involved in the manipulation of host tissue and metabolism, like auxins and cytokinins, would allow pointing out the key processes involved in either the success or failure of plant manipulation as in other plant-gall-inducer systems (e.g., Tokuda et al 2013). …”
Section: Fine Characterization Of the Wpa-poplar Interactions And Thementioning
confidence: 99%
“…Galls are induced only on leaves which are newly expanding during leafhopper feeding, but not on leaves already developed or those which expand after the removal of leafhoppers (Ofori and Francki 1983;Ohata 1993;Matsukura et al 2009b). The degree of gall induction depends on the density and duration of feeding by C. bipunctata (Matsukura et al 2009a;Matsukura and Matsumura 2010;Tokuda et al 2013).…”
Section: Introductionmentioning
confidence: 99%